Benjamin Disraeli Letters : 1852-1856, Volume VI - Disraeli, Benjamin, 1804-1881 (Book collections on Project MUSE., 1997)
Benjamin Disraeli, Queen Victoria's favourite prime minister, was, in the words of Robert Blake, 'the best letter-writer among English statesmen.'This, the latest volume in the critically acclaimed Letters of Benjamin Disraeli series, contains or describes 951 letters (784 previously unpublished) written by Disraeli between 1852 and 1856. These years cover his first cabinet post, as chancellor of the exchequer, his attempts as House leader to unify the Conservative party, and his opposition to the Crimean War, both in the House and in his newspaper, The Press. Included are significant runs of correspondence, such as 63 letters (34 previously unpublished) to the 14th Earl of Derby, and 75 letters (none previously published) to Lord Stanley, the future 15th Earl of Derby, as well as more personal ones, such as 59 letters to the eccentric Mrs Brydges Willyams, the 'female Croesus' who offered Disraeli a substantial legacy. These illuminate anew both his public and private life, and show the strength of his resolve to reshape party policies to suit the age of industrialism and free trade. New light is also thrown on other matters, such as the supposed plagiarism in his panegyric on the Duke of Wellington. Ten appendices include full cabinet lists, Disraeli's own reminiscences of the period, and Stanley's remarkable verbatim notes of intimate conversations with Disraeli at Hughenden Manor.